Persepsi Masyarakat Panipahan Terhadap Tuan Syekh Haji Muhammad Sa’id bin Isma’un, 1965-2002 - Sitepu, Khairani Akmal; Sumanti, Solihah Titin; Batubara, Abdul Karim (Local History & Heritage, 2024)
This research examines the Panipahan community's perception of the figure of Tuan Sheikh Haji Muhammad Sa'id Bin Isma'un in Panipahan City, Riau, during the period 1965-2002. The background of this research is the important role of Tuan Sheikh Haji Muhammad Sa'id in the religious and social life of the Panipahan community. The main question asked is how the Panipahan community perceived the contribution and influence of Mr. Sheikh Haji Muhammad Sa'id during this period. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, observation, and document analysis. The results showed that the Panipahan community had a very positive view of Tuan Sheikh Haji Muhammad Sa'id, recognizing his contribution in religious education, moral development, and social conflict resolution. The conclusion of this study is that Tuan Sheikh Haji Muhammad Sa'id is recognized as an influential and respected figure, who has made a significant impact on social and religious development in Panipahan, Riau. The findings strengthen the argument that religious figures have an important role in shaping social and cultural dynamics in local communities.